An intuitive confession: revealing pain through the self-portrait - Dempster, Andrew Mitchell (Auckland University of Technology, 2014)
This project explores experiences of personal pain and sensory visual disturbance through digital photography. It utilises the confession and self-portrait photography to investigate taking personal perceptions of internal bodily experiences and placing them outside the body. The project oscillates between a focus on confession to the self and how this relates to self-care in a cathartic technology of the self, as a confessional ritual of healing, and confession to others. Thus, a critical interest lies in the shifts in the self and seeing oneself as both subject and object. While the project has an autobiographical context, it also aims to raise issues around experiences relating to ongoing pain management.
Keywords: Visual disturbance; Migraine; Confession; Pain; Technology of the self